2012
DOI: 10.1002/syn.21608
|View full text |Cite
|
Sign up to set email alerts
|

5‐HT1B autoreceptor regulation of serotonin transporter activity in synaptosomes

Abstract: Serotonin-1B (5-HT1B) autoreceptors are located in serotonin (5-HT) terminals along with serotonin transporters (SERT), and play a critical role in autoregulation of serotonergic neurotransmission, and are implicated in disorders of serotonergic function, particularly emotional regulation. SERT modulates serotonergic neurotransmission by high-affinity reuptake of 5-HT. Alterations in SERT activity are associated with increased risk for depression and anxiety. Several neurotransmitter receptors are known to reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 61 publications
4
54
0
Order By: Relevance
“…In fact, increases in serotonin release have been seen in the brains of mice following 5-HT 1A autoreceptor knockdown with siRNA during tests of depressive behaviors, despite an absence in baseline differences (Ferres-Coy et al, 2013). Another potential mechanism through which 5-HT 1B autoreceptors could modulate anxiety and depression-like behavior is via effects on SERT function, given the impact of 5-HT 1B autoreceptors on the regulation of SERT activity and expression (Hagan et al, 2012;Montanez et al, 2014). While there were increases in levels of 5-HT in the hippocampus in ePet-Cre+ mice following inhibition of SERT function with SSRIs, preliminary studies showed no differential effect of SSRIs on behavior (Supplementary Figure S3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, increases in serotonin release have been seen in the brains of mice following 5-HT 1A autoreceptor knockdown with siRNA during tests of depressive behaviors, despite an absence in baseline differences (Ferres-Coy et al, 2013). Another potential mechanism through which 5-HT 1B autoreceptors could modulate anxiety and depression-like behavior is via effects on SERT function, given the impact of 5-HT 1B autoreceptors on the regulation of SERT activity and expression (Hagan et al, 2012;Montanez et al, 2014). While there were increases in levels of 5-HT in the hippocampus in ePet-Cre+ mice following inhibition of SERT function with SSRIs, preliminary studies showed no differential effect of SSRIs on behavior (Supplementary Figure S3).…”
Section: Discussionmentioning
confidence: 99%
“…While the majority of research has focused on serotonin 1A (5-HT 1A ) autoreceptors, evidence also points to serotonin 1B (5-HT 1B ) autoreceptors as a major regulator of serotonin transmission and emotionality (Donaldson et al, 2014;McDevitt and Neumaier, 2011;Richardson-Jones et al, 2010). In rodent models, activation of 5-HT 1B receptors decreases serotonin levels through effects on release, synthesis, and reuptake (Hagan et al, 2012;Hjorth et al, 1995;Trillat et al, 1997). Additionally, 5-HT 1B R knockout mice have increased levels of 5-HT, compared with wild-type mice, following administration of a selective serotonin reuptake inhibitor (SSRI) (Knobelman et al, 2001;Malagie et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…ERK1/2 may be involved in the regulation of SERT by 5-HT 1B receptors. These receptors have been shown to increase 5-HT uptake in vitro as well as in vivo in rat hippocampus (Daws et al, 1999(Daws et al, , 2000Hagan et al, 2012;Montanez et al, 2014), and although it has not been demonstrated which signaling cascade exerts these effects, researchers have shown that 5-HT 1B robustly activates Kinase Modulation of Biogenic Amine Transport ERK2 in CHO cells, and this activation is significantly greater than that of 5-HT 1A receptors, which do not seem to impact SERT activity (Mendez et al, 1999). In studies examining the transporter specificity and ERK1/2 dependence of salvinorin A modulation of DAT via KORs, Kivell et al (2014) found that cells cotransfected with KOR and SERT cDNAs supported salvinorin modulation of 5-HT uptake, but in a direction (inhibition) opposite to that seen with DAT (stimulation).…”
Section: Regulation Of Serotonin Transporter By Erk1/2mentioning
confidence: 99%
“…The 5-HT1B receptor is an important player in 5-HT synaptic homeostasis functioning as a presynaptic autoregulatory receptor to decrease 5-HT synthesis and release [4] in key brain areas such as hippocampus and entorhinal and frontal cortex. The 5-HT1B receptor also stimulates SERT [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The 5-HT1B receptor also stimulates SERT [4,5]. Of note, the 5-HT1B receptor also serves as a heteroreceptor and activation inhibits cholinergic output [6].…”
Section: Introductionmentioning
confidence: 99%